Influence Of Instructional Materials on Pre-Primary Learner’s Acquisition of Science Skills in Tharaka North Sub -County - Ngaine, Felix Gitonga; Koech, Peter Kibet (IOSR Journal Of Humanities And Social Science, 2019)
The Government recognizes pre-school education as one of the educational cycles which can lay a firm, healthy foundation for children during the formative years. The purpose of this study was to establish the influence of instructional materials on children’s acquisition of science skills in pre-primary schools in Tharaka North Sub- County, Tharaka Nithi County, Kenya. This study was based on Active learning theory by Lev Vygotsky. This study utilized a mixed methodology entailing qualitative and quantitative. The target population in this study was 1780 subjects comprising 95 early childhood teachers, 95 head teachers and 1590 pre-school children. Using stratified random sampling the researcher selected 10 teachers from the zones accounting for 10% representation of the target population making a total of ten, the sample of teachers. The instruments for data collection were questionnaires for teachers and head teachers and observation checklist for the children. Piloting of the instruments was carried out in Meru South Sub- County where they were pre-tested to the selected Early Childhood Children. Before data collection, the instruments were administered only once to a sample of 2 teachers and 2 head teachers in two preprimary schools. Cronbach Alpha analysis was computed, to establish the reliability of the instruments, and a coefficient of 0.83 was obtained, and hence the instruments were deemed reliable. As for the content and construct validity of the instruments, the development was done with guidance of the supervisors. The quantitative data was presented in tables, bar graphs, and pie charts. Qualitative data was analyzed thematically by use of themes derived from the responses. The study established that the teachers were of the opinion that the available learning resources not adequate for enhancing the children learning of science activities. There was a strong association between the independent variables and the dependent variables. Based on the findings of the study, the researcher recommends that; The School management, through the county government should lobby for funds that will enhance the pre-schools acquire enough and most appropriate science teaching materials, which will aid in teaching science